Domain wall energy and strain in Pt/Co/Ir thin films on piezoelectric transducers. (31st July 2018) - Shepley, P M; Burnell, G; Moore, T A
Abstract: We study the energy and creep velocity of magnetic domain walls in perpendicularly magnetised Pt/Co/Ir thin films under strain. We find that the enhancement of domain wall creep velocity under strain from piezoelectric transducers is largest in films with the thinnest Co layers (0.56 nm), in which the strain causes the smallest relative change in perpendicular magnetic anisotropy and the largest relative change in domain wall creep velocity. We show how domain wall energy is predictive of the sensitivity of domain wall creep velocity to changes in strain, and thus provide a route to designing magnetic thin film systems for optimum strain control.